Peningkatan Produktivitas Kerja Melalui Penguatan Pemahaman Aqidah bagi Pekerja Roya Perkulakan di Mantingan Ngawi Jawa Timur - Ihsan, Nur Hadi; Huda, Annisa Nurul; Fauziah, Afifah; Rahmawati, Aisyah; Silmi, Nadaa Afifah; Taufiqurrahman, Taufiqurrahman (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance workers’ productivity by strengthening their understanding of aqidah, thereby fodtering intrinsic motivation that promotes dedication, honesty, and responsibility in the workplace. The implementation method involved interactive counseling conducted in six sessions, which included a pre-test, material presentation, and a post-test. The participants were 13 workers from â€œRoya Perkulakanâ€ in Mantingan, Ngawi, East Java, with the material focusing on strengthening aqidah, worship practices, and the application of Islamic values in daily life. The data analysis technique used was quantitative analysis with a One Group Pretest-Posttest experimental design to measure changes in program outcomes. The result of this activity indicated an improvement in aqidah understanding from 49% before the program to 96% after its implementation. This improvement demonstrated that aqidah plays a significant role in improving work productivity. A strong understanding of aqidah shapes workers into individuals who are honest, disciplined, and responsible, thereby contributing to enhanced productivity and work quality.